Harry Potter and the chamber secrets ([s.l.] Warner Bros, 2002)
Fiction films
Feature films
VCD
Screenplay by Steve Kloves, based on the novel by J.K. Rowling, produced by David Heyman, directed by Chris Columbus
Daniel Radcliff, Rupert Grint, Kenneth Branagh
Keywords: Fantasy films